Effectiveness of retention program towards employee’s turnover rate at Stats ChipPac Malaysia / Norsalmiah Kamaruddin - Kamaruddin, Norsalmiah (2011)
An objective for this research is to study the effectiveness of retention program towards employee turnover rate at Stats ChipPac Malaysia. The respondents selected were60 of staff that works there. 43.3% of the respondents were male and 56.7% female. Five variables identified as retention program and only one which are health care benefit not significant with the dependent variable. Salary, career development opportunity, recognition and work/life balance are significant with turnover rate at Stats ChipPac Malaysia with strong or very strong coefficients correlation statistically significant at 0.000. Health care matter is not significant towards the objective. The major factor that influenced the turnover rate at Stats ChipPac Malaysia is career development opportunity and recognition. Cronbach’s alpha coefficient size indicated that career development opportunity, recognition, health care and work life balance are more than 0.5 and the result is reliable and consistence while salary is less than 0.5 means that the result is not reliable and inconsistence. There are 4hypotheses that can accept the alternate and rejected the null which are salary, career development opportunity, recognition and work/life balance. Only one independent variable rejected the alternate and accepted null which is health care. In this research, researcher used correlation only to know the simple relationship between independent variable and dependent variable. There are two recommendations as 2 major factors that influenced the turnover rate at Stats ChipPac Malaysia. First is provide mentor for career development opportunity and second is intangible reward for recognition. Both of the recommendations is simple but less cost and give high impact to reduce employee turnover rate at Stats ChipPac Malaysia.